1991
DOI: 10.1295/polymj.23.297
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Aromatic Poly(ether sulfone)s by Nickel-Catalyzed Coupling Polymerization of Aromatic Dichlorides

Abstract: ABSTRACT:Aromatic poly(ether sulfone)s were prepared by the nickel-catalyzed coupling polymerization of aromatic dichlorides containing ether sulfone structures. Polymerizations were carried out in N,N-dimethylacetamide (DMAc) in the presence of nickel chloride, zinc, triphenylphosphine, and bipyridine and produced aromatic poly(ether sulfone)s with inherent viscosities up to 0.38 dig-1 under mild conditions. The effects of various factors, such as amount of catalyst, ligand, zinc and solvent, reaction tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…Poly(ether ether sulfone)s 2 were chosen by Colon as the first system to be studied because they are generally amorphous and soluble in dipolar aprotic solvents such as N,N-dimethylacetamide (DMAc) and 1-methyl-2-pyrrolidinone (NMP) at the relatively low temperatures (70 °C) required to produce high polymer. Further studies of this system, 3 in addition to a variety of poly(arylene ether ketone)s, have been investigated by Ueda et al 4 Ueda utilized Ni(0) coupling of aromatic dichlorides containing ether-ketone structures to prepare high molecular weight poly(arylene ether ketone)s. This method proved advantageous compared with conventional methods because of the high rates and the mild conditions of the reaction.…”
Section: Price Codementioning
confidence: 99%
“…Poly(ether ether sulfone)s 2 were chosen by Colon as the first system to be studied because they are generally amorphous and soluble in dipolar aprotic solvents such as N,N-dimethylacetamide (DMAc) and 1-methyl-2-pyrrolidinone (NMP) at the relatively low temperatures (70 °C) required to produce high polymer. Further studies of this system, 3 in addition to a variety of poly(arylene ether ketone)s, have been investigated by Ueda et al 4 Ueda utilized Ni(0) coupling of aromatic dichlorides containing ether-ketone structures to prepare high molecular weight poly(arylene ether ketone)s. This method proved advantageous compared with conventional methods because of the high rates and the mild conditions of the reaction.…”
Section: Price Codementioning
confidence: 99%
“…Sulfonated monomer for flame retarding materials was prepared by Robeson and Matzner [ 24 ] the pioneering scientists in this field. Recently, Ueda et al [ 25,26 ] reported the sulfonation of 4,4′-dichlorodiphenyl sulfone and other researchers [ 27–34 ] modified this procedure for the disulfonation of monomer.…”
Section: Introductionmentioning
confidence: 99%
“…3 Ueda et al 4 have reported the synthesis of aromatic poly(ether sulfone)s from nickel complex-mediated aromatic coupling polymerization of aromatic dichloride. An alternative way of making poly(arylene sulfone)s involves oxidation of poly(arylene thioether)s with hydrogen peroxide in formic acid.…”
Section: Introductionmentioning
confidence: 99%